Interferon gamma-induced transcription of the high-affinity Fc receptor for IgG requires assembly of a complex that includes the 91-kDa subunit of transcription factor ISGF3. - Pearse, R N (1993)
A 39-nt DNA sequence, the interferon gamma (IFN-gamma) response region (GRR), is necessary for the IFN-gamma-induced transcription of the high-affinity Fc receptor for IgG (Fc gamma RI) and sufficient for the IFN-gamma-induced transcription of transfected plasmids. By using extracts from IFN-gamma-treated cells, three protein complexes will assemble in vitro on a 9-nt core region in the 3' domain of the GRR. The sequence of this core resembles the IFN-gamma-activated sequence (GAS) described for the GBP gene. Mutations in this GAS core region prevent complex assembly and result in the loss of IFN-gamma induction of reporter constructs containing the mutation. In addition to the GAS core region, a 5' region of the GRR is necessary for optimal IFN-gamma induction and for formation of one of the DNA-protein complexes. By antibody reactivity, we show that a 91-kDa protein, first identified as a component of ISGF3, the IFN-alpha-induced transcription complex, is present in at least two of the DNA-protein complexes. IFN-alpha can induce the formation of the faster-migrating 91-kDa protein-GAS complex but not the slower-migrating complex. Furthermore, IFN-alpha does not result in appreciable transcriptional activation of Fc gamma RI or constructs containing the GRR. Thus, these data demonstrate that the IFN-gamma-activated 91-kDa protein is required for IFN-gamma induction of Fc gamma RI and suggest that an additional complex may be required for optimal expression and specificity.